Highly linear, compact and cost-effective sensor probes for displacement measurements using range-resolved interferometry - Kissinger, Thomas; Wiseman, Kieran B.; Tatam, Ralph P. (EUSPEN, 2021)
We demonstrate a novel approach for interferometric displacement and vibration sensing using range-resolved interferometry (RRI). The concept exploits the ability of RRI to reject the signal contributions due to multiple reflections that would otherwise lead to high levels of periodic non-linearity errors, allowing the use of very compact and cost-effective sensor heads based on gradient index (GRIN) lenses, with the presented approach thought to be widely applicable across many precision engineering applications.